Early outcome of acute peripartum cardiomyopathy in eastern part of Nepal - Nepal, Rajesh; Bista, Madhav; Ghimire, Sita (Nepalese Heart Journal, 2017)
Background and Aims: Peripartum cardiomyopathy (PPCM) is an uncommon complication of pregnancy with variable outcome. There is paucity of data related to its outcomes in Nepal. We studied the clinical and echocardiographic outcome of PPCM patients in eastern part of Nepal.Methods: In this prospectively designed study all patients admitted with the diagnosis of acute severe PPCM at Nobel Medical College, Biratnagar, meeting the inclusion criteria over a period of 14 month, were enrolled and followed up for 3 months post partum.The LVEF and Left ventricular end diastolic dimension (LVEDD) was assessed by echocardiography at baseline and 3 months postpartum. Mortality and survival with normal or depressed ejection fraction were determined. Predictors of outcome were evaluated. Statistical analysis were done using SPSS version 17.Results: Mean age of the study population was 27.6}5.6 years. Ninety five percent of patient had term delivery. Sixty four percent were primigravida. Eighty four percent had the symptoms onset in post partum period. Pulmonary edema was present in 64% during first hospital admission. Mortality was 9% during 3-month follow up period. Thirty six percent had complete recovery of LVEF at 3 months. Fifty five percent survived with depressed LVEF. Age, LVEF less than 30% and LVEDD more than 60 mm at study entry did not correlate significantly with poor clinical recovery at 3 months.Conclusion: This study demonstrates that survival outcome is better even in the patients with severe acute PPCM with early diagnosis and proper management of heart failure.